Peligros en la tipificación de Recomendaciones como Práctica Anticompetitiva en la Ley peruana - Quintana Sánchez, Eduardo (2015)
On this paper, the author disserts on the notion of recommendations as a method of collusion. First, he approaches it based on comparative law (Europe and Latin-America) and precedent case law from INDECOPI, followed by defining how the term is (and should be) understood in Peruvian regulations as a horizontal agreement (cartel). It also analyzes in which instances said application has been inaccurate and the issues surrounding it. Finally, the author illustrates the complexity of framing recommendations as vertical agreements in the absence of “collusion between two or more parties”